If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 52 + -1(2c + 3) = 4(3 + 7) + c Reorder the terms: 52 + -1(3 + 2c) = 4(3 + 7) + c 52 + (3 * -1 + 2c * -1) = 4(3 + 7) + c 52 + (-3 + -2c) = 4(3 + 7) + c Combine like terms: 52 + -3 = 49 49 + -2c = 4(3 + 7) + c Combine like terms: 3 + 7 = 10 49 + -2c = 4(10) + c Multiply 4 * 10 49 + -2c = 40 + c Solving 49 + -2c = 40 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. 49 + -2c + -1c = 40 + c + -1c Combine like terms: -2c + -1c = -3c 49 + -3c = 40 + c + -1c Combine like terms: c + -1c = 0 49 + -3c = 40 + 0 49 + -3c = 40 Add '-49' to each side of the equation. 49 + -49 + -3c = 40 + -49 Combine like terms: 49 + -49 = 0 0 + -3c = 40 + -49 -3c = 40 + -49 Combine like terms: 40 + -49 = -9 -3c = -9 Divide each side by '-3'. c = 3 Simplifying c = 3
| 2(4-5x)=-15x+10 | | s^3-3s^2=5 | | -12p=240 | | 4(3v+7)= | | -100+4*90= | | 71-3x=51 | | 5x-3=2x+8+1 | | 2x+75=4x+91 | | 10z+8m-5z-2= | | -1=2x^2+2x^2+2 | | 7x+14=2x+2 | | -38v-114=-41v-321 | | x+1/2+x+2/3+x+3/4=16 | | 29=8y+(-3) | | t=3s+18.95 | | 13=6+1 | | -1=x^2-5x+2 | | 5x+(-9)=26 | | 1=24-5b | | 186+26b=16b-224 | | 4w+4X+13y+6w+8x-8y= | | 9.9=3x+4.2 | | 25=-3+7r | | 3(y-4)+5=4(y+2)-2y-6 | | 5m-8=-23 | | s^3-2s^2=1 | | -0.26+1.2x=2.28x+1.9 | | -12-5z=37 | | 467.14=180+0.98x | | (4x^3)-(15x^2)=0 | | 17c-2=2c | | 15x=42 |